Behavior of moment-resistant frames after shear-axial failure of reinforced concrete column - Bicici, Erkan (Pontificia Univ Catolica Chile, Escuela Construccion Civil, 2025)
Failure or collapse of entire structure triggered by a local element level failure can be defined as progressive collapse. The degradation and loss on the capacity of an element leads new load path on the structure which creates new load carrying mechanism. The most common approach is sudden removal of the column and pushdown analysis. In this study, a new method is proposed to simulate progressive collapse of reinforced concrete structures. The proposed method includes the shear-axial interaction of reinforced concrete columns and consideration of axial shortening of columns due to lateral strength degradation. The proposed method may be applicable for the progressive collapse analysis of a concrete structure under earthquake. The proposed method is tested in 2D and 3D typical benchmark reinforced concrete frames. The behavior of the frames calculated by the proposed method are compared with the results obtained from pushdown analysis to validate the accuracy of the model. A good agreement is observed between the proposed method and pushdown analysis. The shear-axial interaction method sufficiently covers the behavior of frame analysis with sudden loss of a column. Thus, the proposed method simulates more realistic failure under cyclic loading such as earthquakes.
Keywords: Reinforced concrete columns; progressive collapse; shear failure; frame analysis; concrete structures